Neo-Characterization in the Neo-Victorian Novel - Georges LETISSIER (E-REA)
The purpose of this study is to initiate a reflection on a poetics of second degree characters within the frame of neo-Victorian fictions to document some migrations by confronting such critical approaches as narratology, reception theory, psychoanalysis, historical epistemology, gender and gay and lesbian studies. Hopefully, this cursory, panoramic overview might shed some light on the centrality of character (character-building, -skewing, -bending, -sapping and so forth) in operating a shift from Victorian characterization to what may be designated as neo-Victorian neo-characterization; i.e. a renewed return to a familiar novelistic cast. It will be argued that the neo-Victorian character functions as a memory trigger for a synthetized reading experience, hovering between the mimetic – through the replication of a form of historical faithfulness – and the spectral, by being poised between life and death, presence and absence.